Seasonal reproduction and sexual size dimorphism of the African helmeted turtle, Pelomedusa subrufa (family Pelomedusidae) - Strydom, Aliki V. (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2001.